ROOT HAIR DEFECTIVE SIX-LIKE class I genes promote root hair development in the grass Brachypodium distachyon - Kim, C; Dolan, L (Public Library of Science, 2016)
Genes encoding ROOT HAIR DEFECTIVE SIX-LIKE (RSL) class I basic helix loop helix proteins are expressed in future root hair cells of the Arabidopsis thaliana root meristem where they positively regulate root hair cell development. Here we show that there are three RSL class I protein coding genes in the Brachypodium distachyon genome, BdRSL1, BdRSL2 and BdRSL3, and each is expressed in developing root hair cells after the asymmetric cell division that forms root hair cells and hairless epidermal cells. Expression of BdRSL class I genes is sufficient for root hair cell development: ectopic overexpression of any of the three RSL class I genes induces the development of root hairs in every cell of the root epidermis. Expression of BdRSL class I genes in root hairless Arabidopsis thaliana root hair defective 6 (Atrhd6) Atrsl1 double mutants, devoid of RSL class I function, restores root hair development indicating that the function of these proteins has been conserved. However, neither AtRSL nor BdRSL class I genes is sufficient for root hair development in A. thaliana. These data demonstrate that the spatial pattern of class I RSL activity can account for the pattern of root hair cell differentiation in B. distachyon. However, the spatial pattern of class I RSL activity cannot account for the spatial pattern of root hair cells in A. thaliana. Taken together these data indicate that that the functions of RSL class I proteins have been conserved among most angiosperms-monocots and eudicots-despite the dramatically different patterns of root hair cell development.